Human Resource Management Strategy In Handling Turnover Using A Design Thinking Approach In Aquaculture Startup Companies - Alfian, Nurkholis; Zulaikha, Ellya; Yusak Anshori, Mohamad (Jurnal Ekonomi dan Bisnis, 2024)
A startup company must have resilience in facing various challenges, including operational issues such as employee turnover. Human Resource Management (HRM) plays a crucial role in controlling the activities and operational productivity of the company. This research aims to identify employee responses and the causes of issues related to human resources problems (employee turnover) in the company. The method used in this research employs the Design Thinking approach, which involves the stages of empathy, define, ideate, prototype, and test. The empathy stage is conducted by gaining a deeper understanding of the problem through situation analysis, questionnaire surveys, and interviews. In the define stage, the identification of in-depth problem exploration results in the formulation of a point of view on the problem, and questions (how might we) are created to explore as many ideas as possible. The accumulated ideas are then selected through DOT Voting to choose the best idea. The selected idea in this study is a mental health program for employees expected to reduce employee turnover rates. The resulting prototype is a meditation program for employees. Testing the program yields satisfying feedback, with employees enjoying and feeling their well-being accommodated by the company. Therefore, this program can enhance employee productivity and foster a healthy mind and soul.